Transcriptome analysis of copper homeostasis genes reveals coordinated upregulation of SLC31A1, SCO1, and COX11 in colorectal cancer. Issue 8 (8th July 2016) - Barresi, Vincenza; Trovato‐Salinaro, Angela; Spampinato, Giorgia; Musso, Nicolò; Castorina, Sergio; Rizzarelli, Enrico; Condorelli, Daniele Filippo
Abstract : Copper homeostasis and distribution is strictly regulated by a network of transporters and intracellular chaperones encoded by a group of genes collectively known as copper homeostasis genes (CHGs). In this work, analysis of The Cancer Genome Atlas database for somatic point mutations in colorectal cancer revealed that inactivating mutations are absent or extremely rare in CHGs. Using oligonucleotide microarrays, we found a strong increase in mRNA levels of the membrane copper transporter 1 protein [CTR1; encoded by the solute carrier family 31 member 1 gene ( SLC31A1 gene)] in our series of colorectal carcinoma samples. CTR1 is the main copper influx transporter and changes in its expression are able to induce modifications of cellular copper accumulation. The increased SLC31A1 mRNA level is accompanied by a parallel increase in transcript levels for copper efflux pump ATP7A, copper metabolism Murr1 domain containing 1 (COMMD1), the cytochrome C oxidase assembly factors [synthesis of cytochrome c oxidase 1 (SCO1) and cytochrome c oxidase copper chaperone 11 (COX11)], the cupric reductase six transmembrane epithelial antigen of the prostate (STEAP3), and the metal‐regulatory transcription factors (MTF1, MTF2) and specificity protein 1 (SP1). The significant correlation between SLC31A1, SCO1, and COX11 mRNA levels suggests that this transcriptional upregulation might be part of a coordinated program of gene regulation. Transcript‐level upregulation of SLC31A1, SCO1, and COX11 was also confirmed by the analysis of different colon carcinoma cell lines (Caco‐2, HT116, HT29) and cancer cell lines of different tissue origin (MCF7, PC3). Finally, exon‐level expression analysis of SLC31A1 reveals differential expression of alternative transcripts in colorectal cancer and normal colonic mucosa. Abstract : Intracellular copper levels and distribution are strictly regulated by a network of transporters and intracellular chaperones encoded by a group of 'copper homeostasis genes' (CHGs). Transcriptome analysis reveals coordinated upregulation of the SLC31A1 gene (encoding the copper transporter 1) and other CHGs in colorectal cancer. Such data can be interpreted as suggesting that cancer cells have a greater copper requirement linked to their increased proliferation and survival.